(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Kinilow Satu sub-district, where the community gets irrigation water from rivers, during the long dry season some of these irrigation water sources cannot meet all water needs because the existing drainage system is only able to serve certain areas located around the main canal. During the rainy season, excess water will be stagnant and even floods will occur which will seriously disrupt agricultural activities. The purpose of this PKM activity that can provide a new method to the Nawanua Water-Using Farmer community regarding designing and building an environmentally irrigation network system by channeling excess irrigation water to nearby rivers. The output of the program is environmentally irrigation network system design that is adequate for the people of Kinilow Satu Subdistrict, especially the Nawanua farmer community, as well as additional mastery of applicable knowledge that can be used by the community after implementing the program.